1999
DOI: 10.1046/j.1365-4362.1999.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly vs. fortnightly intralesional meglumine antimoniate in cutaneous leishmaniasis

Abstract: One hundred and four patients with a clinical diagnosis of cutaneous leishmaniasis (CL) and a positive Giemsa‐stained smear for the parasite were recruited after informed consent into this randomized clinical trial, comparing the efficacy of weekly vs. fortnightly intralesional injections of meglumine antimoniate. Patients having more than five lesions and pregnant women were not included. The patients were randomly divided into two treatment groups. Patients in group A were treated with weekly and those in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 10 publications
4
16
0
1
Order By: Relevance
“…MA in this study was similar to the studies by Sadeghian et al [26], Asilian et al [27], Mujtaba and Khalid [31], and Faghihi and Tavakoli-kia [32].…”
Section: Discussionsupporting
confidence: 91%
“…MA in this study was similar to the studies by Sadeghian et al [26], Asilian et al [27], Mujtaba and Khalid [31], and Faghihi and Tavakoli-kia [32].…”
Section: Discussionsupporting
confidence: 91%
“…The failure rate (in terms of exacerbations, partial response, reactivation after primary healing, or any complications) was calculated as 72.9% in group A compared with 39.7% in group B. By contrast, other topical treatment studies in which paromomycin/methylbenzethonium chloride ointment was applied twice daily for 10–20 days have reported a 74.2% cure rate 5 . However, because of the appreciable rate of local reactions to the paromomycin/methylbenzethonium chloride formulation (40% had burning, pruritus and even vesicles) reported by Soto et al.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous systemic and topical therapies available for CL indicate the lack of a single ideal therapeutic agent. One of the generally recommended treatments is intralesional meglumine antimoniate, delivering high concentrations of the drug locally and preventing the systemic toxic side‐effects of this drug 5 . One previous study demonstrated a 95% cure rate using 0.2–0.4 mL of sodium stibogluconate intradermally three times a week for a total of 15 injections 6 …”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] It should be mentioned that the interval for intralesional MA or SSG injections in control arms of each of these 3 studies was 2 weeks, which is not the most appropriate interval for intralesional treatment with pentavalent antimonies. 13 Only mild adverse effects, including postinflammatory hypopigmentation or hyperpigmentation, were reported in approximately 5% of treated patients. [37][38][39] Other treatments…”
Section: Cryotherapy Alone or In Combination With Other Treatmentsmentioning
confidence: 99%
“…3,59 Last but not least, they are relatively expensive, especially when a 2-to 3-week systemic administration is required. 13 Most countries in which Old World CL is endemic are developing ones and are devoid of the required technologies for production of the drugs; thus they must import their needed drugs. As a whole, this process places a significant burden on their budget for health expenses.…”
Section: Pentavalent Antimoniesmentioning
confidence: 99%